All-Cause Mortality and Causes of Death in the Swiss Hepatitis C Cohort Study (SCCS). (25th July 2020) - Roelens, Maroussia; Bertisch, Barbara; Moradpour, Darius; Cerny, Andreas; Semmo, Nasser; Schmid, Patrick; Müllhaupt, Beat; Clerc, Olivier; Semela, David; Junker, Christoph; Negro, Francesco; Keiser, Olivia; et al.
Abstract: Background: With direct-acting antiviral agents (DAAs), mortality rates and causes of death among persons with hepatitis C virus (HCV) infection may change over time. However, the emergence of such trends may be delayed by the slow progression of chronic hepatitis C. To date, detailed analyses of cause-specific mortality among HCV-infected persons over time remain limited. Methods: We evaluated changes in causes of death among Swiss Hepatitis C Cohort Study (SCCS) participants from 2008 to 2016. We analyzed risk factors for all-cause and cause-specific mortality, accounting for changes in treatment, fibrosis stage, and use of injectable drugs over time. Mortality ascertainment was completed by linking lost-to-follow-up participants to the Swiss Federal Statistical Office death registry. Results: We included 4700 SCCS participants, of whom 478 died between 2008 and 2016. The proportion of unknown causes of death decreased substantially after linkage, from 42% to 10%. Leading causes of death were liver failure (crude death rate 4.4/1000 person-years), liver cancer (3.4/1000 person-years), and nonliver cancer (2.8/1000 person-years), with an increasing proportion of cancer-related deaths over time. Cause-specific analysis showed that persons with sustained virologic response were less at risk for liver-related mortality than those never treated or treated unsuccessfully. Conclusions: Although the expected decrease in mortality is not yet observable, causes of death among HCV-infected persons have evolved over time. With the wider use of DAAs, liver-related mortality is expected to decline in the future. Continued monitoring of cause-specific mortality will remain important to assess the long-term effect of DAAs and design effective interventions.